2018
DOI: 10.1002/elan.201800649
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Amperometric Readout Mode of Ion‐selective Electrodes under Potentiostatic Conditions

Abstract: Amperometric responses of all‐solid‐state ion‐selective electrodes, recorded under potentiostatic conditions, were studied on example of potassium‐selective sensors with polypyrrole solid contact, at potential corresponding to reduction of the solid contact material and accompanying transfer of potassium ions across the membrane. Selective and stable in time linear dependences of current vs. logarithm of analyte concentration were recorded, resulting from high membrane resistance and changing membrane potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Jaworska et al. explored the amperometric responses of solid-state ISEs, recorded under potentiostatic conditions . They used potassium-selective electrodes with polypyrrole (PPY) as an ion-to-electron transducer for their study.…”
Section: New Ion-selective Readout Principles and Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaworska et al. explored the amperometric responses of solid-state ISEs, recorded under potentiostatic conditions . They used potassium-selective electrodes with polypyrrole (PPY) as an ion-to-electron transducer for their study.…”
Section: New Ion-selective Readout Principles and Methodologiesmentioning
confidence: 99%
“…Jaworska et al explored the amperometric responses of solid-state ISEs, recorded under potentiostatic conditions. 44 They used potassium-selective electrodes with polypyrrole (PPY) as an ion-to-electron transducer for their study. The potential value was chosen to force the reduction of PPY and transfer of potassium ions across the membrane.…”
Section: Analytical Chemistrymentioning
confidence: 99%
“…From the sensitivity viewpoint the coulometric mode is by far superior to the classical potentiometric readout where the sensitivity of the ISE response to species is limited by the value of the Nernst factor On the other hand, coulometric measurements require a relatively long time to accumulate the signal. From this point of view, the use of the current value instead of that of charge, as the analytical signal, may be advantageous [79]. However, a change of the solution composition requires time.…”
Section: Herementioning
confidence: 99%
“…The constant potential coulometry method invented in the Bobacka’s group opened new opportunities for the use of ion-selective electrodes (ISEs) [ 1 , 2 , 3 ]. Originally, the features of the method were studied with K + -selective ISEs as a model system [ 1 , 2 , 3 , 4 ]. Further studies showed that this method can be used for quantification of divalent cations Ca 2+ , Pb 2+ , and Cu 2+ [ 5 , 6 , 7 ], and NO 3 − , SO 4 2− , and ClO 4 − anions [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%